APPLICATION OF THE SECURE HASHING ALGORITHM (SHA) METHOD AND ROLE-BASED ACCESS SECURITY AUTHENTICATION IN LARAVEL 7 - Mary., Thomson; Pernanda, Anggri Yulio; Junaidi, Satrio (STKIP PGRI Sumatera Barat, 2021)
Information systems that are well made will produce applications that have optimal performance for all accesses to the system. The problem that is often encountered is a system that is easy to hack and tamper with entering from the login system, causing the system to experience data security failure and is accompanied by very dangerous file and database damage. The Laravel Framework provides access security that is Progressive, Scalable and Community Framework to be developed by information system developers, but for the default system from Laravel 7 it is still not enough to provide a solution for data security and access levels for users. Then additional systems are needed in the form of: Secure Hashing Algorithm (SHA), Multi Level Access Algorithm (MLA) and Middleware Checking Access System to overcome data security problems, access and system damage. Testing on the modified login system from the Laravel 7 framework this study has been successful to map users, their access levels, block SQL injection and secure data access accordingly